Análisis ortográfico y ortopográfico en la redacción de noticias de diario El Río en el cantón Babahoyo - Feijoo Feijoo, Kerly Mariuxi (2020)
In the following case study, an orthographic and ortho-typographic analysis will be carried out, by means of which the quality of writing that El Río newspaper issues for its respective target will be determined and in a general way to be able to determine which variables are met, or in the opposite case, what are the shortcomings so that the media can correct and provide its audience with better information as the main objective. The regulations that govern the language are the fundamental basis for defining a good syntax in spelling writing and an aesthetic style that can define the professionalism of both the environment and the professionals who work in their area of competence. Generating trust and loyalty for those who acquire the product constantly in search of staying informed about events at the local and international level, educating those who do not have access to other means of communication that are in full swing of technology and innovation. As the investigation progresses, it is possible to visualize some techniques that provide relevant information about the medium, to obtain the results proposed in the objective through a detailed analysis that will be observed in the printed issue of the copies of the newspaper during a certain period of time.